TRAINING ON COCONUT FIBER (COCOFIBER) PRODUCTION IN UJONG BLANG VILLAGE, ACEH BESAR REGENCY: PELATIHAN PEMBUATAN SERAT SABUT KELAPA (COCOFIBER) DI DESA UJONG BLANG KABUPATEN ACEH BESAR - Endiyani; Wahyu Maulidan; Sri Agustina; Magfirah; Ika Rezvani Aprita (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2026)
Coconut fiber (cocofiber) is a natural fiber from coconut husks that is strong, flexible, lightweight, water-resistant, and versatile. It is used in products such as ropes, mats, carpets, seats, and composite construction materials (boards or concrete reinforcement) because of its unique properties. It is also used as a planting medium because it can maintain moisture and aeration. This community service activity aims to provide training on producing coconut fiber (Cocofiber) in Ujong Blang Village, Aceh Besar Regency. The community gains more knowledge on how to use agricultural commodities, namely coconut fiber waste discarded around their living environment, to produce a more useful product, namely coconut fiber (Cocofiber). The community of Ujong Blang Village is very enthusiastic about processing coconut waste, namely coconut fiber, into cocofiber. With this community service activity, the residents’ knowledge has grown, and it is hoped that they can use cocofiber products for personal use or for sale, thereby increasing their family income.